Current Problems of Membership and Development of the Institutional Structure of the Council of Europe (Summary) - T. A. Antsupova (Московский журнал международного права)
The article indicated by the problems of the International Procedural Law paradigm; provided the author’s concept of a broad understanding of the Council of Europe procedural law. The place of the constituent process as a kind of legal process of the Council of Europe was defined. It was identified the basic steps of the constituent process: 1) confer powers on the Council of Europe by States according to the constituent treaty 2) formation of the system of Statutory bodies and specialized agencies, preparation and distribution of the budget, and 3) the reform of the institutional system and maintain its viability and effectiveness.